Case reportEruptive xanthomas - Zaremba, Joanna; Zaczkiewicz, Andrzej; Placek, Waldemar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Xanthomas are localized lipid deposits in the skin, tendons and subcutaneous tissue associated with lipid abnormality. The hyperlipidemia responsible for this disorder can be caused by a primary genetic defect, a secondary disorder, or both. That kind of skin exanthema may be the first signal of cardiovascular risk. We present a 24-year- old woman with a skin eruption that had appeared a few months earlier.